A psychometric assessment of a self- efficacy eating consumption scale - Palacios, Jorge (2017)
Background: We evaluated the reliability, factorial validity and criteria validity of a psychometric test designed to measure eating behavior self- efficacy. Materials and methods: This construct was measured using a 21 item scale appplied to a sample of 300 between 14 and 74 years (M=29.89), from the Metropolitan Area of México City, Mexico. Results: Data analysis revealed a four factor structure with high reliability. These factors characterized 4 different types of eating behaviors: 1) high fat eating consumption; 2) healthy eating consumption; 3) sweets consumption and 4) drink consumption. Additionally, we measured physical activity as a factor that could be related with healthy eating. Conclusion. We analyzed feasibility of using this psychometric tool to assess self-efficacy in our sample and its potential implication for nutritional programs. It is also considered feasible to apply this scale in new settings, such as educational programs on nutrition and in the nutritionist practice, since it can provide a predictive tool for eating behaviors.